Indicators of Good Governance: Developing an Index of Governance Quality at the LGU Level - Rosario G. Manasan; Romualdo Gaffud; Eduardo T. Gonzalez (Philippine Institute for Development Studies (PIDS), 1999)
Governance is a complex concept. It includes the state's institutions and structures, its decision-making process, its capacity to implement guidelines and the relationship between government officials and the public. Hence, this study attempts to develop a composite index of the quality of governance at the local government level. It also defines limited indicators, which can be measured consistently and can capture the substance of each dimension and their compatibility over time and space. The governance quality index constructed here is focused on three principal elements: capacity of the LGU to mobilize and utilize resources, efficiency and effectiveness of the LGU in the delivery of social services and presence of mechanism to ensure accountability.
Keywords: 330; governance; local revenue; micro level accountability